2013
DOI: 10.1063/1.4829735
|View full text |Cite
|
Sign up to set email alerts
|

Two-frequency heating technique at the 18 GHz electron cyclotron resonance ion source of the National Institute of Radiological Sciences

Abstract: The two-frequency heating technique was studied to increase the beam intensities of highly charged ions provided by the high-voltage extraction configuration (HEC) ion source at the National Institute of Radiological Sciences (NIRS). The observed dependences on microwave power and frequency suggested that this technique improved plasma stability but it required precise frequency tuning and more microwave power than was available before 2013. Recently, a new, high-power (1200 W) wide band-width (17.1-18.5 GHz) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…7 Formerly, the TrapCAD was successfully used for the interpretation of the fluctuation of the highly charged ions one of the injected rf frequency. 10 The code is based on the one electron approach neglecting the particle-particle interactions. Circularly polarized plane wave is assumed to be propagating along the chamber axis.…”
Section: Resultsmentioning
confidence: 99%
“…7 Formerly, the TrapCAD was successfully used for the interpretation of the fluctuation of the highly charged ions one of the injected rf frequency. 10 The code is based on the one electron approach neglecting the particle-particle interactions. Circularly polarized plane wave is assumed to be propagating along the chamber axis.…”
Section: Resultsmentioning
confidence: 99%
“…The KLY was used daring output power of 0 to 1200 W (blue dot). Two-frequency heating method [8,9,10] was used from 1300 to 2000 W (red dot). Dotted line shows requirement values.…”
Section: Beam Test At the Nirs-hec Ion Sourcementioning
confidence: 99%
“…Between 1998 and 2013 numerous experiments were carried out at NIRS; in each experiment a positive effect of the second microwave was demonstrated. 21 The mechanism is still not completely clear. Our basic observation is that when the primary microwave power increases, the plasma shows instability.…”
Section: B Two-frequency Heating Techniquementioning
confidence: 99%
“…Some recent observations of the additional frequency dependence suggested that an electron orbit effect might play some role. 21 One approach to verify or to reject this assumption is a computer simulation. Calculations by the TrapCAD code have continued.…”
Section: B Two-frequency Heating Techniquementioning
confidence: 99%